KONSEP UNIVERSITAS DAN TUJUAN PENDIDIKAN ISLAM SINERGI UNTUK MENCIPTAKAN INSAN KAMIL - Zaid Muhammad Abduh; Asep Rahmatullah (As-Sulthan Journal of Education, 2026)
This article critically examines the concept of the university from an Islamic perspective and its synergy with the objectives of Islamic education in cultivating the insan kamil (the complete human being). Modern universities, shaped by secular paradigms, tend to separate knowledge from moral and spiritual values, producing graduates who are academically competent yet ethically deficient. This study employs a qualitative library research approach by analyzing the Qur'an, Hadith, and classical as well as contemporary literature on Islamic education. The findings reveal that the Islamic university is an integrative institution founded upon tawhid, harmonizing knowledge, faith, deeds, and adab (proper conduct) as the core of the educational process. The objectives of Islamic education extend beyond academic and professional achievement to the formation of individuals who are knowledgeable, morally upright, and responsible as servants and vicegerents of Allah. Therefore, Islamic universities should function not only as centers of knowledge development but also as institutions for character formation and civilizational advancement. The study highlights the need for epistemological and institutional reconstruction to establish a holistic educational system that promotes public welfare and responds effectively to contemporary civilizational challenges.